The widespread use of face masks during COVID-19 pandemics: a literature review (Research, Society and Development, 2020)
With the COVID-19 pandemic, preventive measures of contagion were included, bringing about several radical changes in the daily lives of the population. This study aimed to present what is known about the widespread use of face masks during the pandemic as a preventive method for COVID-19. A review of the scientific literature was carried out, discussing controversies about the use of facial masks, seeking to elucidate about its efficiency and why it should continue to be used. It is evident that at the beginning of the pandemic, the population had an increased sense of fear, which resulted in greater collaboration with preventive measures, such as the use of masks, hand hygiene, social distance, among others; the collaboration and popular belief with these measures was shown to be related to that disseminated by government officials and other entities of popular impact, such as the media. It is believed that the use of facial masks is capable of reducing the transmission of COVID-19, even though it is not a totally effective method, since it depends directly on the high popular adhesion, on the confection material and on the practice of other preventive attitudes for achieve its greatest effectiveness.